PSYCHOLOGICAL CULTURE OF FUTURE EVENT MANAGERS: MANAGERIAL SKILLS - Kot, Galina (PSYCHOLOGICAL JOURNAL, 2018)
The article is devoted to the system of psychological managerial skills, which helps to maximize the level of managerial efficiency development and formation of the psychological culture of future event managers. The purpose of the article is to construct a space of psychological characteristics of professionally significant skills and, with its help, the development of psychological mechanisms for improving the effectiveness of leadership in the field of culture and leisure. As a result of the study of literature, judgments about the skills of managers, which on the semantic level (hypothetically) contain the largest psychological component, were selected. Professionally significant skills and abilities as a psychological factor of effective management implies a higher level of personal skills development, which is manifested at the marginal level of automation of key advertising skills based on the use of psychological knowledge and patterns, and spontaneous adaptability in their practical application and easy situational modification. Professionally significant skills and abilities are considered as a separate scale for measuring the degree of managerial mastery skills development. The system of psychological skills of the event manager is an integrative style that combines stereotyped choices of styles in certain types of managerial situations. The categories of managerial skills and their components are in system interaction, and the specific actions of managers - is a systemic effect of the interaction of skills at the moment. A significant problem in the formation of specific skills is that due to the characteristics of the typical learning process, the growth of skills stops at the first level of the scale of the level of development of skills − intellectual acquainted, that initially not realized, and then causes disappointment studies. The real skill requires a large number of repetitions, which within the educational process provides only training. That is, the actual problem of the formation of psychological culture, both methodical and organizational − in the absence of a learning process of full-scale system trainings. It is necessary to admit that existing models of teaching with prevailing of lectures, seminars and even workshops actually generate managerial dilettantism, limiting skills at the lowest level in the scale of skill − at the level of information acquaintance. The real problem of forming the psychological culture of the event managers is the problem of developing and implementing systematic training psychological technologies for the development of managerial skills.